Optimalisasi Keterlibatan Konsumen melalui Augmented Reality dalam Pemasaran Digital: Kasus Aplikasi IKEA Place - Setyawan, Adhita Arif; Amanda, Fadila; A.S, Muhammad Prakarsa (Journal of Practical Computer Science, 2024)
The development of digital technology has brought significant changes in the way companies build relationships with their consumers. One innovation that is increasingly popular in the world of digital marketing is the use of Augmented Reality (AR) technology. This study aims to analyze how AR can be used to optimize customer engagement through interactive and immersive experiences. This study uses a descriptive qualitative approach with literature study methods, observation of IKEA Place app features, and semi-structured interviews with a number of active app users. IKEA Place was chosen as a case study because it is one of the pioneers in the application of AR in marketing furniture products. The results showed that AR technology in the application was able to increase consumer confidence in the product, facilitate visualization before purchase, and create a fun and personalized experience. In addition, the emotional engagement built through AR interactions also encourages long-term consumer loyalty. This finding indicates that AR is not only a visual aid, but also an effective experiential marketing strategy. The contribution of this research lies in the focus of analyzing consumer emotional engagement through AR interaction, which has not been widely reviewed in previous studies. The main difference from other studies is the specific selection of the IKEA Place case study, as well as the data triangulation approach (literature, observation, and interviews) to describe the user experience holistically. This research not only highlights the technology, but emphasizes the role of AR in building long-term relationships with consumers through meaningful and personalized experiences. This research provides recommendations for digital businesses to adopt AR to create added value and competitive differentiation in the digital economy era.